Exchange rate responses to macroeconomic announcement on the COVID-19 pandemic - Rahmatullah, Dedy; Ghuzini, Diny (Jurnal Ekonomi dan Bisnis, 2023)
This study examines the effects of macroeconomic announcements on the USD/IDR exchange rate before and during the COVID-19 pandemic, and the difference between the impact of positive and negative announcements on the exchange rate. To measure the macroeconomic announcement, a surprise component is used, that is the difference between actual data and market forecasts. The data in this research are daily time series from 1 January 2014 to 30 November 2020. The actual data and market forecasts for each indicator are obtained from Bloomberg. To test the exchange rate response to the macroeconomic announcement, the Ordinary Least Square (OLS) analysis method is used with heteroskedasticity and autocorrelation consistent (HAC). This study finds that during the COVID-19 pandemic, the USD/IDR exchange rate is more sensitive to the surprise component of the macroeconomic announcement compared to the period before the COVID-19 pandemic. This research also finds evidence that positive Indonesian news and negative US news have a significant effect on changes in the USD/IDR exchange rate.